PENGARUH PENAMBAHAN MEKAINISME PEMUTAR PADA LAJU PEMBALIKAN TELUR TETAS - Sunaryo Sunaryo (Teknoin, 2015)
One of the success factor for hatching egg was egg turning on home made egg hatcher classification. These were average four egg turnings needed to hatching egg during 70% days of hatching times. For egg turning, if conducted one by one, there were opportunities off falling off, moreover leads to failure and longer period of time. Using hollistic approach on egg turning, that were added on egg turning tools, the egg turning can be done as whole series in less than two seconds.